PeranPemerintah Daerah dalamPengelolaanDesaWisataBerbasisKearifanLokalpadaDesaWisataSudaji, KecamatanSawan, KabupatenBuleleng - Candra Dewi, Ni Luh Septia; Supriliyani, Ni Wayan; Winaya, I Ketut (CITIZEN CHARTER, 2018)
ABSTRACT Tourism in Bali can be the center of tourism in Indonesia, this is due to the many tourism potentials that are owned, such as the potential of nature, culture and customs which are increasingly developing to attract tourists. Tourism Village is one of the efforts tourism development that was managed by the local government, in this case the Buleleng Regency The purpose of this study is determine the role of government in managing local wisdom-based on tourism villages in Sudaji Tourism Village, Sawan District, Buleleng Regency. The unit of analysis of this study is the Tourism Office of the Buleleng Regency and this study used descriptive qualitative methods. The results of this study indicated that in the management of the Tourism Village Sudaji the role of the government is quite good and is still experiencing some obstacles, both in its management and implementation in the field. Keywords: Role, Tourism Village, Local Wisdom